POST-ELECTION DISORDER SYNDROME: AN ANALYSIS OF COMMUNITY STRESS LEVELS AND MENTAL HEALTH DISORDERS FOLLOWING THE 2024 INDONESIAN ELECTION IN NORTH SULAWESI: Post-Election Disorder Syndrome: Analisis Tingkat Stres dan Gangguan Mental Masyarakat Pasca Pemilu Indonesia 2024 di Sulawesi Utara - Frangky Benyamin Kandioh; Erens Prensius Sanggelorang; Preysi Sherly Siby; Daniel Stevanus Imanuel Sondakh; Joni Kutu’ Kampilong; Gretha Paduli (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study aims to analyze the stress and mental disorders experienced by the people of North Sulawesi after the 2024 General Election, using a mixed-methods approach that includes quantitative and qualitative data. Through surveys and in-depth interviews, this study explores the phenomenon of Post-Election Disorder Syndrome (PEDS), as well as socio-political factors that contribute to increased stress. The study population consisted of 400 respondents, who were interviewed using stratified random sampling, while purposive sampling was used to interview community leaders and health workers. Stress measurements were carried out using the Perceived Stress Scale (PSS-10) questionnaire and in-depth interviews to obtain subjective perspectives of the community. Data analysis used descriptive, inferential, and thematic analysis statistical methods. The results showed that the majority of respondents experienced high levels of stress, with symptoms such as anxiety, sleep disturbances, Difficulty concentrating, and excessive emotional reactions. Social media was also found to have a significant role in exacerbating community stress. This study suggests the need to improve mental health services and public education on managing stress, especially in areas exposed to major political events such as elections. These findings are expected to provide further insight into the psychological impact of post-election in Indonesia.